2017
DOI: 10.21273/hortsci12469-17
|View full text |Cite
|
Sign up to set email alerts
|

Chemical and Sensory Properties of Greenhouse Tomatoes Remain Unchanged in Response to Red, Blue, and Far Red Supplemental Light from Light-emitting Diodes

Abstract: In addition to photosynthesis, light is a critical mediator of secondary metabolism in plants, signaling the production of potentially health-promoting phytochemicals and regulating the emission of volatile organic compounds (VOCs) that can alter the sensory perception of a tomato. Light-emitting diodes (LEDs) are a viable way to test the effects of individual wavebands of light and are being quickly adopted by the greenhouse tomato industry. However, studies characterizing the effects of specific wave… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 57 publications
1
12
0
Order By: Relevance
“…The cultivation systems-either glazing or additional LED interlighting-did not significantly affect the TA content or the a-value or the hue angle from the fruits but were shown to be cultivar-dependent. Dzakovich et al [39], found that supplementary lighting from red, blue, and far red LEDs did not significantly affect the physiochemical or sensory properties of greenhouse tomatoes. They suggest that fruits that were harvested in a time were solar DLI (daily light integral) contributing substantially to the total amount of the light received by plants, may reduce the effect of supplemental lighting.…”
Section: Yield Parameters Fruit Quality Attributes Total Phenolic Con...mentioning
confidence: 99%
See 1 more Smart Citation
“…The cultivation systems-either glazing or additional LED interlighting-did not significantly affect the TA content or the a-value or the hue angle from the fruits but were shown to be cultivar-dependent. Dzakovich et al [39], found that supplementary lighting from red, blue, and far red LEDs did not significantly affect the physiochemical or sensory properties of greenhouse tomatoes. They suggest that fruits that were harvested in a time were solar DLI (daily light integral) contributing substantially to the total amount of the light received by plants, may reduce the effect of supplemental lighting.…”
Section: Yield Parameters Fruit Quality Attributes Total Phenolic Con...mentioning
confidence: 99%
“…Several studies about different additional lighting or light spectra and their influence on yield or fruit parameters have been published [10,39], but no publication about the effect of single glazing or double glazing on fruit quality could be found. We took a closer look at the factors glazing and supplemental LED interlighting and investigated a variety of parameters that influence taste and aroma, as well as yield parameters, the nutritional value of the fruits, and how they are affected by these two factors.…”
Section: Effects Of Single Glazing and Double Glazing And Additional ...mentioning
confidence: 99%
“…Looking at qualitative parameters, while most of the analyzed studies associated supplemental lighting with positive effects (increasing TSS by 6% and Asc by 11%), some inconsistent results were also found. Accordingly, Dzakovich et al ( 2015 , 2017 ) reported that supplemental lighting did not increase the TSS values. Similarly, supplemental lighting on tomato plants was not associated with increased TSS values or Asc contents (Lu et al, 2012b ) or with the sugar or acid contents, according to Gautier et al ( 2005 ).…”
Section: Discussionmentioning
confidence: 97%
“…The results showed that the highest studied green percentage (39%), which was similar to the sunlight spectrum, showed the best effects on plant biomass and yield, suggesting that plants may use sunlight-combined wavelengths more efficiently for growth than other wavelength combinations (Kaiser et al, 2019b ). The far-red wavelength was also investigated by several studies on greenhouse tomato supplemental LED lighting (Pepin et al, 2014 ; Hao et al, 2015 , 2016 ; Gómez and Mitchell, 2016b ; Song et al, 2016 ; Dzakovich et al, 2017 ; Fanwoua et al, 2019 ; Ji et al, 2019 ; Kalaitzoglou et al, 2019 ; Kim et al, 2019 , 2020 ; Zhang et al, 2019 ). The far-red ratio, particularly the red:far-red ratio, influences phytochrome regulation and has effects on plant architectural development, flower induction, germination, photosynthetic capacity, and nutrition (Demotes-Mainard et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation